IMPACT OF HYDROLYZED CAMEL´S WHEY PROTEIN CONCENTRATE ON SOFT CHEESE QUALITY - Nafei , Eman; Adel , Ekbal; Elbarbary , Hend; Mohammed , Hamdi (International Journal of Food Sciences, 2022)
Purpose: The current study's aim is to investigate the effect of hydrolyzed whey protein concentrate (WPC) derived from camel's milk on quality and organoleptic properties of soft cheese during refrigerated storage. Methodology: Two concentrations (10 and 20 mg/g) of camel´s WPC and its hydrolysates [pepsin (P) and pepsin-trypsin (P-T) hydrolysates] were incorborated in to soft cheese and their effects on total bacterial, phsychrophilic, aerobic spore formers, coliforms and yeast & mold counts were calculated till end of refrigerated storage peroid. Also, flavour, texture and appearance of treated cheese groups were evaluated compared to control one. Findings: The results revealed that the higher concentration of WPC and its hydrolysates, the more significant decrease in the microbial load and increase the shelf life up to 34th days with P-T hydrolysate (20 mg/g) compared with the control with a shelf-life of 18th days only at refrigerated temperature (4oC).This hydrolysate showed also the highest degree of hydrolysis (DH%) of 34.06% ± 1.53 and protein concentration of 30.72%± 3.16. The maximum score for body, and texture and appearance was recorded for the cheese sample containing P-T hydrolysate (20 mg/g), while the maximum flavour score was recorded to pepsin (P) hydrolysate (10 mg/g), compared with unhydrolyzed WPC concentrations and control soft cheese groups. Unique contribution to theory, practice and policy: This study was conducted to elaborate antimicrobials from camel´s WPC after enzymatic hydrolysis which could serve as a potential natural presrvatives in soft cheese without altering the sensory characteristics.